2016
DOI: 10.1021/acs.langmuir.6b01888
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Au@AgAu Yolk–Shell Cuboctahedra with Well-Defined Facets

Abstract: The synthesis of Au@AgAu yolk-shell cuboctahedra nanoparticles formed by galvanic replacement in a seed-mediated method is described. Initially, single-crystal Au seeds are used for the formation of Au@Ag core-shell nanocubes, which serve as the template material for the deposition of an external Au layer. The well-controlled synthesis yields the formation of cuboctahedra nanoparticles with smooth inner and outer Au/Ag surfaces. The deposition/oxidation process is described to understand the formation of cuboc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 63 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…Hollow nanospheres themselves can also serve as building blocks to assemble suprastructure, even possibly result in [100] Copyright 2016, American Chemical Society. d-f) Reproduced with permission.…”
Section: Nanoparticle Assemblies With Intricate Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Hollow nanospheres themselves can also serve as building blocks to assemble suprastructure, even possibly result in [100] Copyright 2016, American Chemical Society. d-f) Reproduced with permission.…”
Section: Nanoparticle Assemblies With Intricate Nanostructuresmentioning
confidence: 99%
“…Later studies further revealed the intermediate stage of replacement through tomographic analysis, demonstrating the dissolution of Ag and deposition of Au regrading both structural and chemical characterizations. [99,100]…”
Section: Hollow Polyhedrons With Intricate Nanostructuresmentioning
confidence: 99%
“…The synthesis of yolk‐shell nanocages therefore would be of great significance to improve the electrocatalytic activity for electrocatalysis. Unfortunately, the development of these yolk‐shell nanocages is still insufficient, especially in facile and novel strategy for fabricating the highly efficient electrocatalysts with such unique and well‐defined structures, although some yolk‐shell nanocages have been synthesized ,,,,…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Yolk-shell nanomaterials are unique family of these complex architectures. Substantial efforts have been devoted to the develop of this kind of nanomaterials made of carbon, [7,8] metal oxides, [9,10] noble metals, [11,12] and metal sulfides. [13,14] As for catalysis, the yolk-shell constructions have many superior properties compared to solid and core-shell counterparts, as they could provide a typical framework in a nanoreactor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation